Pendataan Guru Madrasah Setelah Simpatika: Transisi Sistem, Kesenjangan Fitur dan Tantangan Operator - Finan Ahsani Taqwim; Zaefa Khatun; Karwadi Karwadi (Assyfa Journal of Islamic Studies, 2026)
This article aims to analyze the constraints in collecting data on madrasah teachers and education personnel and to formulate improvement efforts in the context of data system transition within the Ministry of Religious Affairs. This study employed a qualitative approach with a case study design. Data were collected through semi-structured interviews with operators at the central Ministry of Religious Affairs, operators at the Regional Office of the Ministry of Religious Affairs of the Special Region of Yogyakarta, and madrasah operators, supported by a review of relevant documentation. The data were analyzed thematically through the stages of condensation, categorization, theme identification, and interpretation. The findings show that the unpreparedness of data on teachers and education personnel is not caused by a single factor, but by a combination of system readiness, organizational readiness, and actor readiness. At the system level, problems emerged in the form of the transition from SIMPATIKA to EMIS GTK IMP that was not yet fully mature, incomplete data migration, incomplete features, slow servers, and suboptimal data integration across ministries or institutions. At the organizational level, the problems were reflected in the high workload of operators and the limited number of personnel. At the actor level, the constraints appeared in the varying competencies of operators and the low awareness of teachers and education personnel as data owners. This study recommends a gradual application transition, case-based technical assistance, strengthened helpdesk support, restructuring of operator workloads, periodic data verification by teachers and education personnel, data integration, and the development of processed data dashboards to support data-based policy-making.